How effective is trauma simulation as an educational process for healthcare providers within the trauma networks? A systematic review. (September 2018) - Barleycorn, Donna; Lee, Geraldine A.
Highlights: Trauma simulation is widely acknowledged as an effective education tool. Simulation is particularly useful in improving non-technical skills (NTS), timeliness and task completion. Time to diagnosis and treatment are good surrogate indicators of improved patient care. Observational studies suggest that trauma networks benefit significantly from trauma simulation training. Abstract: Background: Major trauma is a significant public health problem and a leading cause of death for several age groups. To address this issue, Major Trauma Networks were introduced in the UK from 2010, consisting of Major Trauma Centres (MTCs) and a network of linked Trauma Units (TUs). Objective: The aim is to undertake a systematic review to examine how effective is trauma simulation as an educational process for healthcare providers within trauma networks. Methods: The databases searched included Medline, Embase and Cinahl from 2010 to 2016. This time frame was chosen to reflect more contemporaneous research into simulation training since the advent of trauma networks in 2010 and the publication of national trauma guidelines (NICE). Seven observational studies were selected for narrative review. The screening and selection process followed the PRISMA guidance. The method used to assess the selected studies is based on the Scottish Intercollegiate Guidelines Network (SIGN) handbook. Results: Overall, the studies showed benefits of simulation in trauma training, with some statistical evidence that non-technical skills and overall trauma team performance improved after simulation training, which appears to be effective. Although no studies found any specific correlation of simulation- based learning in trauma to wider effects such as patient outcomes, length of stay or morbidity. Some studies have found that time to diagnosis and treatment arising from improved non-technical trauma team skills from simulation, are a valid surrogate indicator of improved patient outcomes. Conclusion: Overall, it is evident from this review that trauma simulation is an effective educational tool, which can aid trauma learning, develop team's non-technical skills and increase task completion, having a positive impact on the trauma network. Trauma units should therefore benefit from increased trauma simulation training and accessibility to repeated simulation based courses or workshops.